(untitled) (Voice of Teacher, 2024)
The paper examines the graphic fiction Tintin in Tibet (1960) of Georges Remi ‘Herge’ from the perspectives of social semiotics. It engages theoretical contributions of Claude Levi-Strauss, Roland Barthes, and Gunther Kress, along with Theo van Leeuwen. Social semiotics studies how signs operate within social contexts, which facilitates meaning through structural oppositions, cultural myths, and multimodal resources. Levi-Strauss’s structuralist anthropology emphasizes binary oppositions like life and death, rationality and spirituality, civilization and wilderness which reveal cultural contradictions as modern myth in Tintin in Tibet. Furthermore, Barthes reveals the transformation of visual and narrative elements, such as snow, Tibet, and the yeti, into ideological myths of purity, spirituality, and compassion, thereby producing second-order meanings. Moreover, Kress and van Leeuwen’s multimodal social semiotics observes Herge’s ‘ligne claire’ style within a grammar of images, analyzing spatial design, framing, and colour as active meaning-making means that supplements verbal dialogue. Furthermore, these perspectives present Tintin in Tibet as a semiotic artifact that has cultural and ideological values, not merely as children’s literature. The paper from the lens of structural, semiotics, and multimodal processes argue that the narrative exaggerates intercultural encounters, the principles of friendship, and the redefinition of human versus non-human boundaries. The study emphasizes the significance of comics as a fertile area for critical semiotic examination combining anthropological, cultural, and multimodal theories. Thus, it emphasizes Tintin in Tibet as a text of persistent human importance.